2016
DOI: 10.1248/cpb.c16-00454
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Branched PEI Binding to Linear DNA

Abstract: Polyethylenimine (PEI) is one of the most versatile non-viral vectors used in gene therapy, especially for delivering plasmid DNA to human cells. However, a good understanding of PEI binding to DNA, the fundamental basis for the functioning of PEI as a vector, has been missing in the literature. In this study, PEI (branched, 600 Da) binding to DNA was examined by isothermal titration calorimetry (ITC), quartz crystal microbalance (QCM) and a complementary set of analysis tools. We demonstrated that a separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…They performed the same ITC tests using PEI 25 kDa instead of 600 Da PEI. This means that a large PEI can attach to DNA multivalently, while the small PEI can be linked monovalently [19]. The study of Lungu, C.N., et al in 2016 on linear and branched PEIs and their spatial characteristics showed that LPEIs modify their geometry easily compared to BPEIs and are more adaptable to a specific binding sites.…”
Section: Peimentioning
confidence: 99%
See 1 more Smart Citation
“…They performed the same ITC tests using PEI 25 kDa instead of 600 Da PEI. This means that a large PEI can attach to DNA multivalently, while the small PEI can be linked monovalently [19]. The study of Lungu, C.N., et al in 2016 on linear and branched PEIs and their spatial characteristics showed that LPEIs modify their geometry easily compared to BPEIs and are more adaptable to a specific binding sites.…”
Section: Peimentioning
confidence: 99%
“…Recently, non-viral vectors, which are highly efficient, have been developed by modifying low molecular weight (600 Da) with a variety of functional groups [19]. Because of the high density of the charge and the so-called ‘sponge-proton effect’, PEI has more advantages over other cationic polymers than other non-viral vectors.…”
Section: Cellular Toxicity and Transfection Ability Of Peimentioning
confidence: 99%
“…The properties of PEI namely the molecular weight, the architecture of the chains or the degree of branching are fundamental parameters in determining the physicochemical characteristics of nucleic acids-PEI complexes. These properties also strongly influence both the cytotoxicity displayed by the complexes and the efficiency of cellular transfection [ 9 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…T2-weighted MRI of SLMNDs-20% showed a strong negative contrast signal as compared with non-magnetic NDs, and SLMNDs-20% could achieve an accumulation to the sidewall of the centrifuge tubes under magnetic force within 20 min (Figure G). Furthermore, SLMNDs-20% were easy to agglomerate with the addition of a small amount of PEI because PEI molecules bound adjacently on the DNA lattice at low concentrations, while they located far from each other on DNA at high concentrations. , When the amount of PEI was above 12 mg [keeping the ratio of nitrogen to phosphorus (N/P) ≥ 3, the agglomeration gradually disappeared (Figure H). Besides, AGE proved that the addition of PEI inhibited the staining of the sponge loaded on pre-SLMNDs-20%.…”
Section: Resultsmentioning
confidence: 99%
“…During the venous circulation, nucleic acids are easily decomposed by nuclease in the blood. Fortunately, many research studies revealed that polyethylenimine (PEI) can not only enhance delivery efficiency and expand expression duration for both in vitro and in vivo nucleic acid transfection but also protect combined DNA from enzyme digestion in the serum, which inspired us to use PEI for protection of the genes loaded on NDs. PEI has a high density of positive charges to interact with the negatively charged cell membranes and internalize itself combined with nucleic acid into the cell through endocytosis.…”
Section: Introductionmentioning
confidence: 99%